Addition of Jackfruit in Making Choux Pastry - Miya Grania Kusumah Intan; Nisa Rahmaniyah Utami (Media Pendidikan Gizi dan Kuliner, 2023)
Jackfruit is a popular fruit in tropical areas, especially in Indonesia; in almost every region, this fruit can be found and has a high economic level. Jackfruit can provide nutrition as a source of minerals, vitamins,s, and calories. The fruit has a soft and ripe texture, but the seeds are also rich in minerals and vitamins. Jackfruit is one of the most widely consumed tropical fruits in Indonesia. This fruit has a savory and sweet taste, is aromatic, and is often used as a base ingredient for various foods, including pastries. The fruit has rough skin, sharp spines, sweet flesh, and a distinctive aroma. Jackfruit can be processed slowly or cooked into various foods and drinks. In this research, the addition of jackfruit aims to determine the effect of adding jackfruit on the taste and acceptance of Choux Paste by the public and to find out whether jackfruit can be used in making Choux Paste. Adding jackfruit can also provide additional nutritional benefits, such as fiber and vitamins from the jackfruit itself. However, adding jackfruit will affect the texture and consistency of Choux Paste, so you need to adjust the proportions and ratio of ingredients to produce good Choux Paste. This research was conducted to analyze the level of liking (taste, aroma, texture, and color) of Choux Paste through organoleptic tests. This research is a type of experimental research with three treatments for the addition of jackfruit, namely control (P1) 50%, (P2) 70%, and (P3) 100%. This research shows that the best formula for adding jackfruit in making Choux Paste, which both panelists prefer, is the addition of 70% jackfruit. The average results obtained from the aspects (color, aroma, taste, and texture) are a total score of 35.8 for the expert panelists with an average of 2.9, which is included in category VII. Meanwhile, the total score of the non-expert panelists was 37.8, with an average of 3.2, which was included in the like category